Nebulized enriched heparin improves respiratory parameters in patients with COVID-19: a phase I/II randomized and triple-blind clinical trial - Ramos da Silva Grillo, Vinicius Tadeu [UNESP]; Bertanha, Matheus [UNESP]; da Silva Rodrigues, Lenize [UNESP]; de Lima, Marcelo Andrade; Mellucci Filho, Pedro Luciano [UNESP]; Rahal Guaragna Machado, Rafael; Durigon, Edson Luiz; Dias Sertorio, Nathália [UNESP]; de Assis Golim, Marjorie [UNESP]; Moroz, Andrei [UNESP]; Marques Braz, Aline Márcia [UNESP]; de Moraes, Leonardo Nazário [UNESP]; et al. (Springer Nature, 2024)
To evaluate the safety and the potential antiviral treatment of inhaled enriched heparin in patients with COVID-19. The specific objectives were to investigate the anticoagulation profile, antiviral and anti-inflammatory effects, and respiratory evolution of inhaled enriched heparin. We conducted a randomized, triple-blind, placebo-controlled Phase I/II clinical trial in hospitalized adults with COVID-19 receiving inhalation of enriched heparin or saline (placebo) every 4 h for 7 days. Among the 27 patients who completed the study, no changes in blood coagulation parameters were observed, indicating the safety of inhaled enriched heparin. The group receiving enriched heparin showed a significant reduction in the need for supplemental oxygen and improvement in respiratory parameters, such as the PaO2/FiO2 ratio. Inhalation of enriched heparin is shown to be safe and has also demonstrated potential therapeutic benefits for patients with COVID-19. These promising results justify the continuation of the study to the next phase, Phase II/III, to further evaluate the therapeutic efficacy of inhaled enriched heparin in the treatment of COVID-19-associated viral pneumonia. Trial registration: ClinicalTrials.gov. 08/02/2021. Identifier: NCT04743011.
Keywords: COVID-19; Enriched heparin; Safety; SARS-CoV-2; Treatment